Fibrin clot properties and their modulation in thrombotic disorders - Undas, Anetta (Thrombosis and Haemostasis, 2014)
Accumulating evidence indicates that accelerated formation of fibrin clots composed of compact, highly-branched networks with thin fibres which are relatively resistant to plasmin-mediated lysis can be commonly observed in patients with venous or arterial thrombosis. This review discusses characteristics of fibrin clot structure and function in patients with various thromboembolic manifestations, in particular myocardial infarction, ischaemic stroke and venous thromboembolism, based on the publications till December 2013. Moreover, factors will be presented that in vivo unfavourably determine altered fibrin clot properties in thrombotic disorders and modalities that can improve clot phenotype.
Keywords: Fibrin clot; fibrinolysis; thrombosis